The Role of Digital Transformation in Improving Employee Performance - Widodo, Singgih Danu (Journal of International Conference Proceedings, 2024)
This research discusses the impact and implications of digital transformation on employee performance and skills at Port services business sector 2 Cirebon. By using quantitative research methods and simple linear regression, the results of this research show that factors such as motivation, ability, knowledge, and expertise, as well as digital transformation, have a positive and significant impact on employee performance. Factors such as effective use of information technology, resource empowerment, work culture, teamwork, employee empowerment, training, information technology, knowledge management, innovation, and creativity also play an important role in improving employee performance. Employees at this company are considered to have the ability to work as a team and complete tasks responsibly and on time. The suggestion from this research is that it is important for leaders and decision-makers to design and implement effective digital transformation strategies, as well as increase understanding of the role of organizational culture and leadership in supporting digital transformation.